Urban Households' Willingness to Pay to Improve Municipal Solid Waste Collection Services and Associated Factors: A Double-Bounded Contingent Valuation Study in Harar City, Ethiopia. (November 2022) - Girma, Haileyesus; Geremew, Abraham; Alemayehu, Molla; Mulatu, Gutema; Gebrehiwot, Mesfin; Defloor, Bart
Municipal solid waste collection (MSWC) service financing is a challenge for governments in developing countries, with little or no contribution from the service users. In most Ethiopian cities, residents do not pay for MSWC. This study aims to estimate households' willingness to pay (WTP) for improved municipal solid waste collection service in Harar city. A cross-sectional study was conducted among 331 households employing the contingent valuation method with a double-bounded dichotomous choice format. The hypothetical program works to collect solid waste twice a week, house-to-house, and safely dispose of it to reduce environmental and health impacts. The Tobit regression model was used to account for the determinants of households' WTP. Findings showed that 89% (95% CI: 85.4, 92.5) of households were WTP for the improved waste collection program, with an average yearly amount of US12. The Tobit model shows that being married ( β = 6.9, 95% CI: 1.2, 13.7), having a monthly household income of >8000 ETB ( β = 31.9, 95% CI: 22.1, 41.7), attending education about MSWM ( β = 11.8, 95% CI: 5.6, 18.1), having temporary storage at household level ( β = 15.3, 95% CI: 9.5, 21.2), and recycling practices ( β = 5.5, 95% CI: 1.2, 10.8) positively influenced the WTP. Interventions like providing educational programs about waste handling and recycling and providing or encouraging households to have temporary storage at the household level are needed to enhance users' WTP. The policy implication of the finding is that community contribution through service fees could be a strategy for sustainable financing.